Physicochemical properties and IgE binding ability changes of turbot allergen during oxidation - LU Zongchao; LI Zhenxing; ZHANG Limin; LIN Hong (浙江大学学报. 农业与生命科学版, 2013)
During food processing and storage, proteins are susceptible to the action of any hydroxyl radicals. Reactive oxygen species (ROS) are naturally generated in food systems. Oxidative processes in food result in decreased quality by causing changes in color, texture, flavor and nutritional value. Currently, many researchers have reported that the proteins are the primary target of oxidizing radicals in vivo. Protein solubility and functional activity reduction were revealed in meat proteins due to simulation oxidation system inducing polymerization and degradation. Furthermore, the effects of metal-catalyzed oxidation systems in fish proteins were also reported.To date, there is no correlation study between protein oxidation and fish allergen. Therefore, the objective of this study was to explore modification of fish muscle proteins by oxidizing radicals, including functional properties such as the allergenicity and functionality groups. To investigate the effects of protein oxidation on the content of carbonyl and sulfhydryl, turbot proteins (allergens) were exposed to a free radical generating system and incubated at 37℃ for different intervals. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) was used to analyze the alterations of turbot proteins. The alterations of the parvalbumin allergenicity were investigated by Western blot with sera from three fish allergic patients and by indirect enzyme-linked immunosorbent assay (ELISA) method with rabbit ant-i turbot parvalbumin polyclonal antibody.The results showed that 27% proteins were precipitated when exposed to the hydroxyl radical oxidation systems for 5 h. The contents of carbonyl groups in supernatant and precipitate increased by 9.7 and 2.0 times after 5 h oxidation, and sulfhydryl groups decreased by 13.5% and 29.1%, respectively. The electrophoretic patterns of control showed that the contents of 12, 26 and 41 ku proteins extremely decreased. However, the contents of 36 ku proteins increased with increasing oxidative time, which suggests that the aggregates might be formed via non-covalent interactions. IgE Western blot indicated that immunogenicity of proteins decreased with increasing oxidation time. Furthermore, indirect ELISA indicated that the immunogenicity of parvalbumin in both supernatant and precipitate decreased by 16.7% and 31.5% after 5 h oxidation, respectively.It is concluded that the oxidation alters the physicochemical properties of turbot proteins (allergens) and this may lead to the modifications of chemical structure and functionalities of the proteins. The chemical changes occur concomitantly with protein functionalities. However, oxidative damage can also cause important loss of quality. This research could help fish researchers and processors to develop strategies to minimize the oxidation reactions in fish foods during storage and processing.